Primary care physicians' experience with zoster vaccine live (ZVL) and awareness and attitudes regarding the new recombinant zoster vaccine (RZV). Issue 48 (19th November 2018) - Hurley, Laura P.; Allison, Mandy A.; Dooling, Kathleen L.; O'Leary, Sean T.; Crane, Lori A.; Brtnikova, Michaela; Beaty, Brenda L.; Allen, Jessica A.; Guo, Angela; Lindley, Megan C.; Kempe, Allison
Abstract: Background: The Advisory Committee on Immunization Practices (ACIP) has routinely recommended zoster vaccine live (ZVL) for adults ≥60 since 2008; only 33% of eligible adults received it by 2016. A recombinant zoster vaccine (RZV) was licensed in 2017 and ACIP recommended in January 2018. Our objectives were to assess among primary care physicians (1) practices and attitudes regarding ZVL and (2) awareness of RZV. Methods: We administered an Internet and mail survey from July to September 2016 to national networks of 953 primary care physicians. Results: Response rate was 65% (603/923). Ninety-three % of physicians recommended ZVL to adults ≥60, but fewer recommended it to adults ≥60 with a prior history of zoster (88%), adults > 85 (62%) and adults ≥60 on low-dose methotrexate (42%). Several physicians recommended ZVL in ways that are not recommended by ACIP including to adults 50–59 (50%), adults ≥60 with HIV (33%), and adults ≥60 on high dose prednisone (≥20 mg/day) (27%). Nineteen percent of physicians stocked and administered ZVL and did not refer patients elsewhere for vaccination, 37% did not stock and only referred patients to receive it, and 44% both stocked/administered and referred elsewhere. Twenty-three % (n = 115) of physicians who had ever administered ZVL in the office (n = 490) had stopped, citing primarily financial issues (90%). Only 5% were 'very aware' of RZV. Conclusions: Physicians report not recommending ZVL to certain ACIP-recommended groups, but report recommending it to some groups for which the vaccine should be avoided. Implementation of recommendations for RZV will need to consider financial barriers and the complex patchwork of office-based and pharmacy delivery ZVL has encountered.